Juventude e Puebla: aspectos teológicos pastorais na evangelização da juventude - Santos, Pamela Karina dos (2019)
The present research aims to give an overview of what evangelization of Youth includes. From an in-depth reflection of what the youth universe is, bringing research from sociologists and youth researchers the goal is to understand that one can not speak of youth only with a restricted view on. From this context, to bring to the study and reflection the proposal of the Episcopal Conference of Puebla and its preferential option for youth and all that this has meant in Latin America and Brazil. And therefore to present a proposal that is capable of meeting the anxieties about evangelization of youth, where it is necessary to understand that for a pastoral action to be coherent, effective and responsible, it must step on the same ground as the youth steps and recognize in it , as well as an ecclesial subject, the loving face of Jesus Christ